Frequency of unsuccessful milkings in automatic milking rotary - Ljunggren, Ida (2015)
Developments in milk production are heading towards fewer but larger herds where the milking process is often fully automated. Automatic milking systems were launched in the 1990’s and in the year 2010 the Automatic Milking Rotary (AMR) was introduced. As a rule there are no supervision personnel present during the milking event in systems with automatic milking. This means that there is a risk that cows can be incompletely milked in one or more udder quarters, for example if the robots fail in attaching the teat cups or if the cow kicks off the milking unit. Incomplete or missed milking can lead to reduced milk yield and/or milk leakage, which can later lead to mastitis. This is important to each dairy farmer’s milk production as well as the udder health of each individual cow. The present study was composed of two experiments. The purpose of Experiment 1 was to investigate the frequency and cause of unsuccessful or incomplete milking in the AMR. Experiment 1 was carried out on a herd of 171 cows and included eight milkings (four days) and one day for recording udder conformation and assessing teat position and condition. The frequency and causes of unsuccessful or incomplete milking were registered in a template. In addition, the possibility of a relationship between milk somatic cell count (SCC) and kick off of the teat cups was investigated. The results of Experiment 1 showed a relationship between udder conformation and failed attachment of teat cups. The results also showed that 82.6% of the milkings in AMR were successful in the 1st milking attempt. A proportions of 37.9% of the failures at cluster/quarter level at 1st milking were repeated at the 2nd milking attempt. The results also showed that 95% of the individual quarters were successfully attached at the 1st milking attempt and that approximately 96% of the milkings, at udder level, were successful when outcome of the 1st and 2nd milking attempts were combined. The primary cause of unsuccessful milkings in the 1st and 2nd milking attempts was failed attachment of the teat cups, mainly on the right back teat. A problem with the automatically recorded data was that 43 milkings were noted as approved by the AMR during the 1st milking attempt even though disturbances, e.g. failed attachment of teat cups, kick off of milking unit, and/or tramp on milking tube, occurred according to the manual monitoring. When these 43 milkings were added to the unsuccessful milkings after the 2nd attempt (60 milkings), the final milking result was 93.1% successful milkings at udder level. Experiment 2 was based on two different treatments, Treatment A and Treatment B, with 11 cows in each treatment group. The cows in the study had SCC ≤ 150 000 cells/ml milk per udder quarter. The purpose of the study was to investigate how one or three purposely omitted milkings on one udder quarter impacted milk yield, lactose content, and milk SCC. The design was a within udder comparison. One udder quarter (right front) was exposed to a treatment, while the adjacent quarter (left front) was the control quarter. Differences between treated and control udder quarter was calculated and tested if the difference differed from zero. Treatment A was carried out for 28 milkings (14 days) and Treatment B for 36 milkings (18 days). Treatment A was based on one purposely omitted milking on right front udder quarter and Treatment B three omitted milkings on right front right udder quarter with three milkings between the omitted milkings. At udder quarter level, a significant difference between front udder quarters were observed in milk yield, lactose content and SCC during the first days after treatment, where milk yield and lactose content decreased while SCC increased in the treated udder quarter. The difference between quarters disappeared at the end of the experimental period. The present study shows the importance for all four udder quarters to be completely milked on every milking occasion. Further development of the AMR and further research on the effects and recovery period of unsuccessful and incomplete milking is needed. Future research should involve a greater number of cows and a wider variation in udder health.